An Assessment of Pregnant Women's Health Literacy and Internet-Based Decision Making. - Bulut, Özlem Ülkü; Kırmızıgül, Ebru İnan; Küçükkelepçe, Didem Şimşek (Lokman Hekim Health Sciences, 2026)
Introduction: This study aimed to examine the relationship between pregnant women's health literacy and their internet-based decision-making. Methods: This descriptive correlational study was conducted between July and December 2024 in the antenatal outpatient clinic of a private hospital. The pregnant women who met the inclusion criteria were selected for the study. The study was conducted on 308 pregnant women. Data were collected through face-to-face interviews using the Descriptive Information Form, the European Health Literacy Survey Questionnaire-Short Form (HLS-EU-Q16), and the Internet-Based Decision-Making Scale in Pregnancy (IDMSP). Data were analyzed using SPSS 22.0 software, employing descriptive statistics and correlation analyses. A p-value of <0.05 was considered statistically significant. Results: The study was completed with 308 pregnant women. The mean age of the participants was 28.94±3.88 years (min=21; max=45), and the mean gestational week was 35.03±2.53 (min=22; max=40). It was found that 52.9% of the pregnant women used the internet for 1-3 hours per day, and 21.1% believed and took into account the information they found online. The average score on the HLS-EU-Q16 was 36.72±6.61 (min=15.48; max=50.00), and the average score on the IDMSP was 32.38±7.05 (min=10.00; max=50.00). A positive but low-level and statistically non-significant correlation was found between total internet-based decision-making scores and health literacy scores (r=0.090, p=0.115). Discussion and Conclusion: Health literacy levels varied according to certain sociodemographic characteristics of pregnant women, and internet use may influence decision-making processes. Improving access to accurate and reliable information during pregnancy can contribute to enhancing health literacy.